Food (di)lemmas: Disentangling the Italian Local Food Policy narratives - Giampiero Mazzocchi; Francesca Giarè; Roberta Sardone; Ilenia Manetti; Roberto Henke; Sabrina Giuca; Patrizia Borsotto (Italian Review of Agricultural Economics (REA), 2023)
Recently, food-related policy initiatives have proliferated, such as food strategies, food plans, food councils, food districts and food communities, just to name the more relevant ones. Far from being systematically defined and logically systematized, these concepts often overlap or are used as synonyms. The paper has systematically traced the current trends showing how these concepts are used in the current debate, the theoretical background on which they are grounded and the public policies they call for, following a threefold approach: (1) a literature analysis to establish the state of academic research on food systems in its multidimensionality; (2) a review of the existing national legislation to detect the utilization of food policy-related lemmas in the normative; (3) a computational linguistic analysis applied on institutional documentation to explore how cities and territories are using concepts and definitions in the grey literature. The results show that the construction of narratives around the topic of food systems planning is experiencing a momentum, with particular emphasis on principles, background premises and governance aspects. In this context, the risk of marginality for the agricultural sector in such discourses and narratives is highlighted.
Keywords: Q18; E61; H70; 330; food policy; Italy; narratives; policy design